Kedudukan Hukum Pekerja Kontrak (PKWT) dalam Hal Terjadi Pemutusan Hubungan Kerja (PHK) Sepihak - Mahfudin Mahfudin; Aturkian Laia (INDO PUBLISHING, 2026)
This research analyzes the legal position of fixed-term contract workers (PKWT) facing unilateral termination of employment in Indonesia, where contract workers occupy a vulnerable position due to time-limited employment relationships. This normative legal research with a descriptive-analytical qualitative approach examines labor regulations, Industrial Relations Court decisions, and related academic studies. The findings indicate that PKWT workers have a different legal position from permanent workers, reflected in their rights upon termination. PKWT workers experiencing unilateral termination before the contract ends are entitled to compensation equal to wages until the contract period (Article 62 of the Manpower Law), while permanent workers are entitled to severance pay and length-of-service rewards. Judicial practice shows that unilateral termination can be declared null and void, with judges considering work continuity that may change PKWT status to permanent employment. The implementation of PKWT workers' rights still faces challenges such as regulatory disharmony, weak supervision, and ineffective administrative sanctions. This research recommends regulatory harmonization, improved supervision, strengthening law enforcement capacity, and formulating uniform national interpretation guidelines.